2011
DOI: 10.1093/gerona/glr209
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Stratification of Elderly Patients in the Emergency Department: A Comparison Between the “Identification of Seniors at Risk” and the “Silver Code”

Abstract: Prognostic stratification of elderly ED patients with the SC is comparable with that obtained with direct patient evaluation. The SC, previously validated in hospitalized patients, predicts ED readmissions and future hospitalizations even in patients discharged directly from the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 16 publications
2
40
0
7
Order By: Relevance
“…Our finding, that the ISAR has a poor discriminating value to predict adverse outcomes in older patients discharged from UK acute medical units, shows that the ISAR did not perform as well as in the original Canadian study [6], where the tool was shown to be 'fair' discriminating value (AUC: 0.71). However, our findings are compatible with more recent European and Asian studies [7][8][9][10][11][12] which have reported areas under the curves for the ISAR between 'no value' (0.5) and 'fair' (0.7). As our study only evaluated the 'best' 40%, further studies are warranted taking 'all comers' before the utility of this tool can be judged.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding, that the ISAR has a poor discriminating value to predict adverse outcomes in older patients discharged from UK acute medical units, shows that the ISAR did not perform as well as in the original Canadian study [6], where the tool was shown to be 'fair' discriminating value (AUC: 0.71). However, our findings are compatible with more recent European and Asian studies [7][8][9][10][11][12] which have reported areas under the curves for the ISAR between 'no value' (0.5) and 'fair' (0.7). As our study only evaluated the 'best' 40%, further studies are warranted taking 'all comers' before the utility of this tool can be judged.…”
Section: Discussionsupporting
confidence: 93%
“…The ISAR includes six simple dichotomous questions, making it simple and acceptable for patients and staff alike. The ISAR has been tested in North America [6], many European countries [7][8][9][10][11] and Hong Kong [12] where its predictive value varied between 'fair' and 'poor' [determined using receiveroperator curve (ROC) analysis which takes both specificity and sensitivity into account], the difference depending upon the case mix and the health services available in different countries. For the ISAR to be used in the UK, it is important to demonstrate adequate predictive ability in UK settings, but this has not yet been done, and this was the purpose of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Seven different geriatric prognostic screening instruments were assessed in the included studies: Identification of Seniors at Risk (ISAR), 9 TRST, 10 the Silver 57,71 were each assessed by two studies involving 464 and 12,451 patients, respectively. The studies evaluated a wide range of outcomes at post-ED time frames ranging from 14 days to 1 year.…”
Section: Screening Instrumentsmentioning
confidence: 99%
“…57 The derivation and validation sets were consistent, but neither threshold was sufficiently prognostic for 1-year mortality. Di Bari et al 71 subsequently evaluated the Silver Code for 6-month outcomes of ED revisits, readmission, mortality, or any combination of these outcomes at the same two thresholds. Again, the Silver Code lacked sufficient prognostic accuracy to increase (LR+ ranges = 1.59 to 2.47) or decrease (LR-ranges = 0.70 to 0.88) the risk of these outcomes.…”
Section: Screening Instrumentsmentioning
confidence: 99%
“…22 Penelitian Salvi, dkk. 23 di Italia mendapatkan mortalitas 30 hari sebesar 6,5% dan mortalitas 6 bulan sebesar 19,5%. Sementara itu, Bari, dkk.…”
Section: Insiden Mortalitas 30 Hari Pasien Usia Lanjut Yang Datang Keunclassified